The use of guselkumab in psoriatic arthritis: evidence from real clinical practice - N. V. Nekrasova; Yu. E. Borovikov; T. G. Zadorkina; P. V. Nekrasova (Современная ревматология, 2021)
Psoriatic arthritis (PsA) is a chronic inflammatory disease of the joints, spine and enthesis from the group of spondyloarthritis that develops in patients with psoriasis. Guselkumab is a biologic disease-modifying antirheumatic drug, an inhibitor of interleukin 23, which has been shown to be effective in the treatment of plaque psoriasis and PsA.Objective: to evaluate the effectiveness of guselkumab treatment in PsA patients.Patients and methods. The study included 16 patients with PsA. All patients received 100 mg of guselkumab subcutaneously at weeks 0, 4, 12, 20. Disease activity and treatment efficacy were assessed at weeks 0, 12 and 24 using the DAS28, ASDAS, BASDAI, DAPSA activity indices, the index of the extent and severity of psoriasis PASI.Results and discussion. During treatment, patients with PsA showed a pronounced positive dynamics of the indices of disease activity and an improvement in the skin condition. Before the treatment with guselkumab, the mean value of the DAS28 index was 4.26±0.64, DAPSA – 37.94±9.45, ASDAS – 2.7±0.65, and BASDAI – 5.49±1.39, after 12 weeks of treatment these indicators decreased to 3.03±0.49; 17.06±4.58; 1.64±0.33 and 3.48±0.66, respectively, and after 24 weeks (after the 4th injection) – to 2.32±0.18; 11.31±2.18; 1.22±0.27 and 2.62±0.78, respectively (p<0.05 for all cases). Before treatment, the average PASI index reached 30.99±15.43, after 12 weeks – 4.55±4.82, and after 24 weeks – 1.05±1.46 (p<0.05). During treatment, a significant improvement in the main manifestations of the disease was noted: regression of peripheral arthritis, spondylitis, and skin rashes.The treatment was well tolerated during the 24 weeks of the study, and no serious adverse events were reported.Conclusion. The data from real clinical practice indicate that guselkumab is highly effective and safe in the treatment of PsA.